Substrate cleavage and duration of action of botulinum neurotoxin type FA ("H, HA"). (1st June 2018) - Pellett, Sabine; Tepp, William H.; Lin, Guangyun; Johnson, Eric A.
Abstract: Botulinum neurotoxin (BoNT) type FA is the only known naturally occurring chimeric BoNT of domains of BoNT/A and BoNT/F. BoNT/FA consists of an F5-like light chain (LC), a unique heavy chain (HC) translocation domain, and a HC receptor binding domain similar to BoNT/A1. Previous analyses of purified BoNT/FA have indicated a 5–10-fold greater potency in cultured human or rat neurons as compared to BoNT/A1 and a 400–500-fold greater potency compared to BoNT/B1. However, in vivo potency in mice was about 5-fold lower than BoNT/A1 or/B1. In this report, species specificity was examined by cell-based assays using primary neurons from mice and examining VAMP1 and 2 cleavage. The data indicated similar potency of BoNT/FA in primary mouse spinal cord neurons as previously observed in primary rat and human induced pluripotent stem cell (hiPSC) derived neuronal cell models, and equal enzymatic cleavage of mouse VAMP1 and 2 isoforms. Since the duration of action of BoNTs is due to continuous enzymatic activity of the LC in the neuronal cytosol, BoNT/FA was expected to have a short duration of action due to its F-type LC. In this report the duration of action of BoNT/FA was compared to that of BoNT/F1, /F5, and/B1 in both hiPSC derived neurons and in the in vivo mouse model. The data indicate a duration of action of BoNT/FA similar to BoNT/B1, while BoNT/F5 had a short duration of action similar to BoNT/F1. Highlights: Botulinum Neurotoxin type FA (H, HA) (BoNT/FA) efficiently enters mouse spinal cord neurons. BoNT/FA cleaves mouse VAMP1 and 2 with equal efficiency. BoNT/FA has a long duration of action similar to BoNT/B1. BoNT/F5 was purified for the first time and has a low specific activity and short duration of action.